Estimated sea ice particulate organic carbon (iPOC) in the Arctic marine food web (1985-2019) - Chelsea Koch; Thomas Brown; Remi Amiraux; Gustavo Yunda Guarin; Lisa Loseto; Doreen Kohlbach; Nigel Hussey; Steve Ferguson; David Yurkowski (Arctic Data Center, 2023)
This dataset is a synthesis of sea ice particulate organic carbon (iPOC) values that were estimated from previously published and new highly branched isoprenoid (HBI) lipid values in Arctic marine organisms. HBIs are produced by several sea ice and pelagic diatom species. Samples were collected for various projects from 1985 through 2019 from the Bering, Chukchi, Beaufort, and Barents Seas and from the Canadian Arctic Archipelago. This dataset includes iPOC values throughout the year (January to December) and was used to investigate year-round utilization of ice algal carbon throughout the marine food web. Multiple trophic levels are represented by benthic invertebrates, zooplankton, ice-associated invertebrates, fish, seabirds and marine mammals.